Coordinated Dynamic Control in the Task Space for Redundantly Actuated Cable-Driven Parallel Robots - Zhang, Bin; Shang, Weiwei; Cong, Shuang; Li, Zhijun (IEEE/ASME transactions on mechatronics, 2021)
Although cable-driven parallel robots (CDPRs) act as parallel mechanisms that are driven by multiple cables coordinately, the coordination motion analysis is often omitted. Therefore, the coordination effect in the task space (TS) of redundantly actuated CDPRs is addressed in this article, and a scheme of the coordinated dynamic control in the TS (CDCT) is proposed to guarantee high-precision control. Additionally, to handle the inevitable external disturbances, the robust analysis is also synthesized in the CDCT scheme, and the stability of the whole control system is proved. Moreover, due to the existing actuation redundancy, the cable tension distribution method is presented to ensure that all cables are always kept in tension. Trajectory tracking experiments are carried out on the redundantly actuated CDPR, and the augmented PD (APD) scheme without coordination and robust effect and the CDCT scheme without robust effect (CDCT-wR) are used for comparisons. The results show that, there is a significant effect of the coordinated control with a better coordination performance by using the CDCT scheme, and the final tracking accuracy has an evident improvement. Besides, the satisfactory robustness of the CDCT scheme in resisting external disturbances is also verified via supplementary experiments.